2022
DOI: 10.1159/000526317
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Inherited Retinal Disease: Long-Term Durability of Effect

Abstract: The recent approval of voretigene neparvovec (Luxturna®) for patients with biallelic RPE65 mutation-associated inherited retinal dystrophy with viable retinal cells represents an important step in the development of ocular gene therapies. Herein, we review studies investigating the episomal persistence of different recombinant adeno-associated virus (rAAV) vector genomes and the pre-clinical and clinical evidence of long-term effects of different RPE65 gene replacement therapies. A targeted review of articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 122 publications
1
16
0
1
Order By: Relevance
“…It is possible that photoreceptors continue to degenerate due to insufficient delivery of functional genes, or that photoreceptors had already reached a pre-apoptotic state at the moment of therapeutic intervention [ 294 ]. A recent review demonstrated that the treatment effects of RPE65 gene therapy lasts up to 7.5 years after administration, which suggests that multiple gene-therapy doses are needed to provide clinical stability during a patient’s lifetime [ 295 ]. A single dose of FDA-approved Luxturna costs approximately USD 425,000 per eye per treatment.…”
Section: Investigational Treatment Modalitiesmentioning
confidence: 99%
“…It is possible that photoreceptors continue to degenerate due to insufficient delivery of functional genes, or that photoreceptors had already reached a pre-apoptotic state at the moment of therapeutic intervention [ 294 ]. A recent review demonstrated that the treatment effects of RPE65 gene therapy lasts up to 7.5 years after administration, which suggests that multiple gene-therapy doses are needed to provide clinical stability during a patient’s lifetime [ 295 ]. A single dose of FDA-approved Luxturna costs approximately USD 425,000 per eye per treatment.…”
Section: Investigational Treatment Modalitiesmentioning
confidence: 99%
“…One major advantage of subretinal gene therapy is that it is generally considered a “one-and-done” approach, which is to say that one application is expected to be sufficient to have continued efficacy over very long periods of time. However, it is probably pertinent to note here that with gene therapies being so early in their development, it is not entirely clear how long efficacy will last, but as of 2022 we have seen 10 years of continued Luxturna expression in animal models and 7.5 years in humans [ 51 ]. Remarkably, the long-term episomal (not integrated into the host cell genome) persistence of transcriptionally active recombinant AAV genomes has been reported, as recently reviewed by Leroy BP et al [ 51 ].…”
Section: Current Principal Administration Routes For Ocular Therapiesmentioning
confidence: 99%
“…Defects in the RPE65 gene lead to canine and mouse models of LCA which have recently been considered as models for gene therapy [394][395][396]. As to date, Voretigene neparvovec-rzyl (Luxturna, Spark Therapeutics, Philadelphia) was approved by U.S FDA for ocular gene therapy of RPE65 in 2017, which transduces some RPE cells with a cDNA encoding normal human RPE65 protein, making it possible to repair the visual cycle [397,398]. Currently, human clinical trials using a similar vector are continuing.…”
Section: Phototransduction and Visual Cycle Pathwaymentioning
confidence: 99%